Conceptual paper on factors affecting the use of online learning - Mat Yaakub, Nuryana Atiqah; Romli, Azizi (2016)
The purpose of this paper is to examine the factors affecting the use of online learning and the theory used in previous studies examined in this study.The methodology that used is conceptual.This paper used secondary data. This paper based of previous study on factor affecting the use of online learning.Expected findings of this study is internet experience can affect the use of online learning and the theory that used is Theory of technology accepting model (TAM).